Transcending Boundaries of Creativity: Active learning in the Design Studio - Mohamed Gamal Abdelmonem (International Journal of Architectural Engineering Technology, 2014)
This essay investigates the changing dynamics of interaction and paradigm of communication in the design studio. It analyses the process of practical implementation of interactive tools in architectural education which placed the diversity of students' cultural experiences, contextual awareness and individual interests as crucial resource for design innovation and inquiry. Building on Brian Lawson's thesis on creativity in design thinking, this research project undertook comprehensive investigation of students' satisfaction of their roles in the studio and the room for liberal thought they are given to elaborate on genuine approach to architectural matters. The cyclical development of interactive learning strategy is explored through two different settings: first, it analyses architectural students' position as passive/active in the studio, considering their relationships with tutors' ideals; second, it reports on empirical strategy of students-led workshops at British schools of architecture, during which students have taken the lead of their creative design agenda. The practical implementation of interactive learning tools proved influential in helping students to personalize their design direction and to build a sense of confidence and independence.